Analysis of immune cell infiltration in the tumor microenvironment of cervical cancer and its impact on immunotherapy - Fei Qin; Lu Huan; Xia Shi; Yuanyuan Hua; Yi Wu (Frontiers in Oncology)
BackgroundCervical cancer remains a leading cause of cancer-related mortality among women worldwide. Despite advances in vaccination and early screening, late-stage diagnoses are common and associated with poor outcomes. This study aimed to identify novel prognostic biomarkers and therapeutic targets through a multi-omics approach, providing insights into the tumor immune microenvironment.MethodsWe integrated transcriptomic, mutational, and clinical data from The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO) to construct a prognostic model. Differential gene expression, enrichment analysis, immune infiltration profiling, and drug response prediction were performed to explore molecular features and therapeutic relevance.ResultsKey high-risk biomarkers (EZH2, PCNA, BIRC5) and protective factors (CD34, ROBO4, CXCL12) were identified. The model effectively stratified patient survival in both cohorts and showed strong predictive performance. High-risk patients displayed distinct immune cell infiltration patterns and upregulated immune checkpoint expression, suggesting potential benefit from immunotherapy. Additionally, higher tumor mutational burden (TMB) was associated with improved survival. Drug sensitivity analysis indicated increased responsiveness of high-risk patients to agents such as Afuresertib and Venetoclax.ConclusionThis study establishes a reliable prognostic model and identifies critical biomarkers associated with cervical cancer progression, offering valuable insights into personalized therapeutic strategies. The findings contribute to a more comprehensive understanding of the disease and provide a foundation for future clinical applications. Nevertheless, further large-scale validation is required to confirm these findings and enhance their clinical utility.